Risk Factor of Posthemorrhagic Hydrocephalus: Cerebrospinal Fluid Total Protein - Wang, Zhiwen; Chen, Yuxin; Zhou, Xinhui; Wang, Changfeng; Chen, Xianjun; Min, Feixiang; Liu, Ruen; Xiang, Hui (Frontiers in Surgery, 2022)
Objective Cerebrospinal fluid total protein (CSF-TP) levels in adults with posthemorrhagic hydrocephalus (PHH) are poorly studied. The objective of this study was to explore the characteristics of CSF-TP levels in patients with PHH. Methods The clinical data of 156 patients with hemorrhagic brain disease were retrospectively studied and divided into PHH and NPHH groups. Single-factor and multi-factor analyses were performed, and the key role of CSF-TP was evaluated using linear analysis. Results Among the 156 patients, 85 (54.5%) had PHH and 34 (21.8%) underwent surgeries. Hypertension (p = 0.017), days [total fever time when body temperature ≥ 38.5°C (p = 0.04)], Glasgow Coma Scale (GCS) score (p < 0.001), and time (from the onset of the disease to the obtainment of CSF-TP after lumbar puncture (p < 0.001) were important factors for PHH. Logistic regression analysis revealed that GCS score < 8 [odds ratio (OR) = 2.943 (1.421–6.097), p = 0.004] and CSF-TP × time ≥ 9,600 [OR = 2.317 (1.108–4.849), p = 0.026] were independent risk factors for PHH. All CSF-TP values were averaged every 2 days. CSF-TP was negatively correlated with time. Linear analysis showed that CSF-TP in the PHH group was higher than that in the NPHH group at the same onset time, and that the duration of detectionin the CSF was longer. Conclusion Cerebrospinal fluid total protein (CSF-TP) × time ≥ 9,600 and GCS score <8 were independent risk factors for PHH. CSF-TP was higher in the PHH group than in the NPHH group.